Nutrition-Sensitive Food Distribution Amidst Inflationary Shock: Evidence from a Randomized Intervention in Egypt - Abay, Kibrom A.; Kurdi, Sikandra (American Economic Association, 2023)
This project aims to evaluate the impact of Egyptian Food Bank’s General Feeding Program (GFP), which provides monthly food packages to ultra-poor households. The food packages are being redesigned to include more diverse and nutrient dense food items. A complementary awareness campaign is being launched to promote and enhance healthy eating habits and food preparation. This study will evaluate the impact of the newly designed food package, both in absolute terms as well as relative to the old food package, as well as the contribution of the complementary messages on various nutritional outcomes, including food insecurity, nutritional intake and beneficiaries’ Knowledge, Attitudes and Practices (KAP). These insights will help in refining the design of the GFP and other complementary programs and can inform the design of food subsidy programs in Egypt and beyond. The evaluation is particularly designed to answer the following broad research questions: (a) Whether the new food basket decreases food insecurity compared to the previous (old) basket and compared to no basket (b) Whether the new food basket increases household and individual dietary quality compared to the previous basket and compared to no basket (c) Whether receiving nutritional messaging with and without the new food basket increases nutritional knowledge and dietary quality? (d) Which households are most likely to benefit more from the GFP and associated complementary interventions? (e) How much does selection of beneficiaries by community-based organizations differ from selection by Proxy Means Test (PMT) scores. (f) Whether targeting based on PMT scores could improve the share of beneficiaries most likely to benefit from the program